Building An Optimal Learning Environment: Inspiring Classroom Management - Lika Widiawati; Neviyarni S; Herman Nirwana (Journal Of Psychology, Counseling And Education, 2024)
The role of teachers in achieving successful learning in schools is highly significant. Classroom management is a key issue associated with optimal learning conditions. The discussion covers definitions, scope, objectives, functions, principles, spatial arrangement, and approaches in an educational context. This study employs library research methods to highlight the importance of classroom management in effective learning. The approach to classroom management involves various strategies, from authority to pluralistic approaches, influencing how teachers handle classrooms and student behavior. In conclusion, effective classroom management is crucial in achieving optimal learning objectives.